استخدام Spin Game لتحسين مهارة الكلام عند الطلبة بـ MIN 3 Aceh Besar - Wilda Qanita; Tarmizi Ninoersy (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
Speaking skill (maharah kalam) remains a challenge in Arabic learning because instruction tends to emphasize theory rather than communicative practice. This study aims to analyze the implementation of an Arabic course program and its contribution to improving students’ speaking skills at Fajar Hidayah School, Aceh. The study employed a descriptive qualitative approach using interviews, observation, and documentation. Participants included students, Arabic teachers, supervisors, and school leaders. The findings show that the program was designed based on students’ needs analysis and implemented systematically through direct methods, interactive media, and continuous evaluation. The program positively improved students’ speaking fluency, vocabulary mastery, and self-confidence in using Arabic. The study concludes that the Arabic course program can serve as a model for intensive extracurricular activities in developing Arabic speaking skills.